Penerapan Fungsi Manajemen Penyiaran Program Talkshow Arah Angin TVRI Nasional - Dani Setiadarma; Laode Muhammad Assegaf (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to analyze the implementation of POAC-based production management functions and the media strategies employed by TVRI. The research method used a qualitative descriptive approach with a constructivist paradigm. Data were collected through interviews, observations, and document studies, then analyzed thematically using source triangulation. The results indicate that the Planning, Organizing, and Actuating functions operate quite well, but the Controlling function remains very weak. Production evaluations are conducted only on a routine administrative basis, without any concrete follow-up that would impact program quality improvement. This indicates a work culture that tends toward formality, resulting in the same weaknesses recurring from one episode to the next. This study recommends the need for a serious, transparent, and quality-improvement-oriented control mechanism so that the Arah Angin program does not simply become routine but can emerge as a reputable public broadcast.